Qualidade de vida subjetiva e satisfação com as condições de consumo: Uma investigação em contextos geográficos nordestinos. - Silva Júnior, Severino Domingos da (2013)
This study analyses consumer s subjective quality of life according to the suposition that its quality is influenced by the satisfaction of consumption access, its preparation and construction, consume of products, satisfaction with public services, necessary ones or leisure ones, satisfaction with the possession of a product, maintenance and repair, and its discard. The study aims to identify and analyse the subjective quality of life and satisfaction conditioned to people who live in the northeast cities of Brazil. Through this analysis, the conditions of quality in northeastern contexto were measured as well the measurement of consumers satisfaction with their consumption conditions according with the availabilty of products and services offered in their cities. For this, it was realized a research with 500 paricipants from the cities of Teresina (PI), Fortaleza (CE), Natal (RN), João Pessoa (PE) e Recife (PE). It was used a quantitative approach by using a descriptive analysis and an exploratory factorial analysis. The data analysis presented through the participants answers and Pearson s and Spearman s coefficient correlations that the adopted hypotheses probably influence in the subjective quality of life. So the sample presented that the satisfaction with the consumption of products and services tend to influence in consumer s perception according to their quality of life. Howver, it was verified through the data analysis that some cities presented huge differences among them. It was probably due to the sample or due to an item which did not represent a local reality. Thereby, this study presents elementary perspectives of marketing which may contribute to the development of quality of life, as well as with public policies as these concepts can be easily introduced into the society as it is indispensable to the knowledge of population, its importance to understand better a society s functioning, its practices which are developed through their social interactions and which impacts are resulted in the consumer s and society s perceived quality of life. In the end, this work is concluded with the presentation of theoretical and practical implications, as well as its limitations and suggestions of new researches related to this theme.